Experimental Study on the Concept of Hollow-Core Photonic Bandgap Fiber Stethoscope - Adel Abdallah (International Journal of Optics)
An experiment is proposed to show the feasibility of using hollow-core photonic bandgap fibers (HC-PBF) in the fiber-optic interferometric stethoscopes to generally improve the sensitivity and overcome the problems associated with the electronic stethoscopes. In the experiment, the HC-1550 is used as a measuring arm of an unbalanced Mach-Zehnder interferometer (MZI) and the conventional single-mode optical fiber (SMF) is used as an isolated reference arm. Detection and demodulation of the relative phase shift is performed passively using phase-generated carrier homodyne technique (PGC). The proposed results indicate the significance of using HC-PBFs in the future stethoscopes.